2003
DOI: 10.1093/chemse/28.5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Androstenone Anosmia

Abstract: It has been estimated that approximately 30% of the population is unable to detect the odor of androstenone. These estimates, however, were made using tests and criteria optimized for identifying detection. Such criteria favor Type II over Type I errors--that is, they are excellent at identifying true detectors at the cost of erroneously labeling some detectors as non-detectors. Because these criteria were used to identify non-detectors, it is possible that the rate of non-detection may have been overestimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…This supports the genetic contribution to the general hyposmia, as suggested recently by Pinto et al (2008). Genetic contribution to variation in detection thresholds (Wysocki and Beauchamp 1984;Gross-Isseroff et al 1992) and in experienced intensity and pleasantness (Keller et al 2007) has been demonstrated for androstenone, an odorant that shows relatively high prevalence of specific anosmia/ hyposmia (20-30%; Wysocki and Gilbert 1989; for a review see Bremner et al 2003), and thus large phenotypic variation. Significant genetic effects have also been found for the detection of isoamyl acetate, an odorant with no known specific anosmia (Gross-Isseroff et al 1992).…”
Section: Discussionsupporting
confidence: 76%
“…This supports the genetic contribution to the general hyposmia, as suggested recently by Pinto et al (2008). Genetic contribution to variation in detection thresholds (Wysocki and Beauchamp 1984;Gross-Isseroff et al 1992) and in experienced intensity and pleasantness (Keller et al 2007) has been demonstrated for androstenone, an odorant that shows relatively high prevalence of specific anosmia/ hyposmia (20-30%; Wysocki and Gilbert 1989; for a review see Bremner et al 2003), and thus large phenotypic variation. Significant genetic effects have also been found for the detection of isoamyl acetate, an odorant with no known specific anosmia (Gross-Isseroff et al 1992).…”
Section: Discussionsupporting
confidence: 76%
“…The latter can manifest as either enhanced sensitivity to an odorant (specific hyperosmia) or as a strongly reduced capacity to smell particular odorants. This diminished sensitivity, also known as specific anosmia, has been reported by several investigators and in connection with a range of odorants (e.g., Amoore, Venstrom, & Davis, 1968;Bremner, Mainland, Khan, & Sobel, 2003;Hirth, Abadanian, & Goedde, 1986;Kendal-Reed, Walker, Morgan, LaMacchio, & Lutz, 1998;Lison, Blondheim, & Melmed, 1980;Lunde, Skuterud, Nilsen, & Egelandsdal, 2008;Meilgaard, 1993;Pelosi & Pisanelli, 1981;Plotto, Barnes, & Goodner, 2006;Snyder, 1931), and recently the first reports confirming a genetic basis for differences in human olfactory phenotypes have emerged (Keller et al, 2007;Menashe et al, 2007). These reports extend previous work, notably twin studies by, for example, Finkel, Pedersen, and Larsson (2001), Segal, Topolski, Wilson, Brown, and Araki (1995), and Wysocki and Beauchamp (1984), indicating heritability in olfactory functioning.…”
Section: Human Olfactionsupporting
confidence: 58%
“…The cooking odour of entire male pigs with boar taint may be evaluated more negatively by androstenone sensitive people (Furnols et al, 2003). Most cooks are female who are up to six times more sensitive to androstenone than men (Bremner et al, 2003). A cook is therefore more likely to detect boar taint than an average consumer.…”
Section: Discussionmentioning
confidence: 99%